THE IMPACT OF SPATIAL VISUAL TASKS IN DESCRIPTIVE GEOMETRY ON ARCHITECTURE STUDENTS’ PROBLEM-SOLVING ABILITIES (American Journal of Pedagogical and Educational Research, 2025)
This article presents a theoretical analysis of how spatial visual tasks in the discipline of Descriptive Geometry influence the problem-solving abilities of architecture students. Drawing on psychological-pedagogical and methodological frameworks, it explores the role of spatial reasoning, graphic cognition, and decision-making processes in architectural education. The research is grounded in the theories of J. Piaget, L. Vygotsky, P. Galperin, and H. Gardner, highlighting the cognitive and pedagogical potential of spatial exercises. The paper theoretically substantiates the effectiveness of Descriptive Geometry as a tool for developing professional competencies and enhancing intellectual performance among architecture students.